Development of surface plasmon resonance imaging for detection of Acidovorax avenae subsp. citrulli (Aac) using specific monoclonal antibody - Chokchai Puttharugsa (2018)
An immunosensor based on surface plasmon resonance imaging (SPR imaging) using a specific monoclonal antibody 11E5 (MAb 11E5) was developed for the detection of the seed-borne bacterium Acidovorax avenae subsp. citrulli (Aac), which causes fruit blotch in watermelons and cantaloupes, and compared to the conventional ELISA technique. The 1:40 mixed self-assembled monolayer (mixed SAM) surface was used for the immobilized MAb 11E5 on sensor surface for the detection of Aac. Both whole cells and broken cells of Aac were tested by using direct and sandwich detection assay. The limit of detection (LOD) of Aac using the SPR imaging technique and a direct detection assay was 10 6 cfu/ml and a subsequent amplification of the SPR signal using a polyclonal antibody (PAb) lowered the LOD to 5×10 5 cfu/ml. The LOD for the ELISA technique was 5×10 4 cfu/ml for the detection of Aac, which was slightly better than that for the SPR technique. However, the sensor surface based on SPR imaging offered a major advantage in terms of surface regeneration, allowing at least five cycles with a shorter time assay, multi-channel analysis with an application on multiplex detection, and an ease of the surface usage for the detection of Aac in the naturally infected plant. The surface was tested against the naturally infected sample and showed good selectivity toward the Aac bacteria. © 2010 Elsevier B.V.